Analisis Perubahan Penggunaan Lahan Pesisir Di Kecamatan Batu Layar, Kabupaten Lombok Barat Pada Tahun 2002 dan 2019 - Mark Johannes Wiggers; I Wayan Nuarsa; I Dewa Nyoman Nurweda Putra (Journal of Marine Research and Technology, 2020)
The coastal zone is a unique region because the coastal area is a meeting place of land and sea. Coastal areas are vulnerable to various human activities that can affect the terrestrial and marine environment both directly and indirectly. This can result in changes in land use, especially in coastal areas. Rapid changes in land use in coastal areas due to the development of tourist areas and the high level of erosion and abrasion that occurs causes the need for planned, comprehensive and sustainable land management planning and regional development. the purpose of this study was to determine land use, land use changes and the level of accuracy of landsat imagery in coastal areas of Batu Layar District, West Lombok Regency. This study uses the Quantum GIS software to analize Landsat satellite imagery data in 2002 and 2019. The results showed that the land use change during of 17 years (2002 - 2019), namely the residential and building classes increased by 237.69 ha and while the bush class , forests, plantations, rice fields, open land and waters respectively decreased by 71.91 ha, 61.2 ha, 46.44 ha, 32.4 ha, 20.79 and 5.04 ha respectively. The Overall Accuracy of this study was 90%.